PERLINDUNGAN DARI GIZI BURUK: KEMITRAAN PENGELOLAAN DATA NUTRISI BALITA DI NASYIATUL AISYIYAH - Norma Sari; Sri Winiarti; Herman Yuliansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2019)
Children are an investment of the nation and the state in the future, so the prevention of malnutrition programs is very relevant to prepare a superior generation. Providing proper nutrition and nutrition data management for toddlers is an effort to protect toddlers from malnutrition. This partnership aims to help partners (1) increase knowledge related to consumer protection for toddler food products, (2) increase knowledge about the prototype of Website-Based Nutrition Applications; (3) increase understanding of healthy eating standards for toddlers; (4) understand and have skills in making nutritious home made food, (5) training in the use of nutrition applications for toddlers can be used by the Nasyiatul Aisyiyah Center Dream. The method used is Focus Group Discussion (FGD) and Training. The results of the partnership show that after the partnership program has been carried out (1) Participants have increased knowledge and are able to analyze key issues related to consumer protection for toddler food products; (2) participants have increased knowledge through Website Based Nutrition Applications and are able to analyze the weaknesses of the application to be improved; (3) Participants better understand the standard of healthy eating for proper consumption for toddlers and provide some analysis to become a sustainable agenda; (4) Participants better understand and have the skills in making nutritious home made foods that are balanced and schedule a national campaign; (5) Nutrition applications can be used by the Nasyiatul Aisyiyah Center for monitoring toddlers nutrition for their members. Keywords: prevention, information technology, management, toddler nutrition